Impact of Telephone-Based Care Coordination on Use of Cessation Medications Posthospital Discharge: A Randomized Controlled Trial. Issue 3 (18th May 2016) - Tague, Caleb; Richter, Kimber P.; Cox, Lisa S.; Keighley, John; Hutcheson, Tresza; Fitzgerald, Sharon A.; Ellerbeck, Edward F.
Abstract: Introduction: Smokers benefit from ongoing cessation support upon leaving the hospital and returning to their home environment. This study examined the impact of telephone-delivered care coordination on utilization of and adherence to cessation pharmacotherapy after hospital discharge. Methods: Inpatient smokers ( n = 606) were randomized to receive counseling with care coordination (CCC) or counseling alone (C) for smoking cessation. Both groups received written materials and telephone-based cessation counseling during hospitalization and postdischarge. CCC recipients received help in selecting, obtaining, and refilling affordable pharmacotherapy prescriptions during and after hospitalization. Study outcomes included self-reported utilization, duration of use, and type of medication during the 3 months postdischarge. Results: Of the 487 (80%) of participants completing 3-month follow-up, 211 (43.3%) reported using cessation pharmacotherapy postdischarge; this did not differ by study arm (CCC: 44.7%, C: 42.0%, p = .55). Use of pharmacotherapy postdischarge was associated with smoking at least 20 cigarettes/day at baseline (odds ratio [OR]: 1.48; 95% confidence interval [CI]: 1.00–2.19) and receipt of pharmacotherapy during hospitalization (OR: 4.00; 95% CI: 2.39–6.89). Smokers with Medicaid (OR: 2.29; 95% CI: 1.32–4.02) or other insurance (OR: 1.69; 95% CI: 1.01–2.86) were more likely to use pharmacotherapy postdischarge than those with no health care coverage. Less than one in four (23.8% of CCC; 22.2% of C) continued pharmacotherapy beyond 4 weeks. Conclusions: Supplemental care coordination did not improve use of postdischarge pharmacotherapy beyond that of inpatient treatment and behavioral counseling. Insurance coverage and use of medications during the hospitalization are associated with higher use of evidence-based treatment postdischarge. Implications: Many hospitalized smokers do not receive the benefits of cessation pharmacotherapy postdischarge and telephone quitline programs often fail to help smokers procure pharmacotherapy. Thus, effective strategies are needed to improve utilization and adherence to evidence-based cessation therapies when smokers leave the hospital. We found that use of postdischarge pharmacotherapy was strongly associated with receipt of pharmacotherapy during the hospitalization and with the availability of insurance to cover the costs of treatment. Additional efforts to coordinate pharmacotherapy services did not improve either utilization or adherence to therapy.